Economic Learning Innovation Through Digital Applications - Ramadanita, Ramadanita; Savitri, Nasya Nurani; Halimah, Siti; Qahfi, Muhammad (Lembaga Penelitian dan Pendidikan Mandala, 2025)
The use of digital technology is starting to be of interest to educators for the continuity of learning with technological advances, teachers are expected to be able to master learning strategies through digital applications, digital technology is expected to be able to improve the learning process. The development of digital technology has changed the educational landscape significantly,One area that feels the impact is economic learning. one of the technological innovations to make it interesting and can help educators easily carry out assessment evaluations. The purpose of this study is to determine whether digital applications can help teachers to increase students' interest in learning. The method used is a qualitative research method with field studies, the results of the study state that digital applications can increase students' interest and motivation to learn so that learning can run as expected.